Pengaruh Strategi Pembelajaran Case Study dan Minat terhadap Hasil Belajar Geografi Siswa Kelas XI SMA N 2 Solok Selatan - Preska Khairani; Ade Irma Suryani; Momon Dt. Tanamir (Departement of Mathematics Education, 2024)
This research aims to determine the differences in learning outcomes of students who use the Case Study learning strategy and students who use conventional learning models. The difference in learning outcomes of students with high interest who use the Case Study learning strategy and students with high interest who use conventional learning models. Based on the results of the research conducted, it was obtained; 1. There is a difference between learning outcomes using the Case Study learning strategy and the conventional model with Fcount of 3.521 and sig 0.00 <α 0.050. 2. There is a difference between the geography learning outcomes of high interest students who use the Case Syudy learning strategy and the conventional learning model with Fcount of 30.877 and sig 0.00<α 0.050. 3. There is a difference between the geography learning outcomes of low interest students who use the Case Study learning strategy and the conventional learning model with Fcount of 15.719 and sig 0.00 <α 0.050. 4. There is an interaction between the Case Study learning strategy and interest in learning as well as geography learning outcomes with Fcount of 6321.014 and sig 0.00 <α 0.050. This means that the student learning outcomes between the experimental class and the control class are different or in other words, there is an influence of the Case Study learning strategy and interest on the geography learning outcomes of class XI students at SMA N 2 Solok Selatan.